2023
DOI: 10.1109/access.2023.3244778
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Resilience Demonstration for Wind Energy Sites in Co-Simulation Environment

Abstract: Sandia National Laboratories and Idaho National Laboratory deployed state-of-the-art cybersecurity technologies within a virtualized, cyber-physical wind energy site to demonstrate their impact on security and resilience. This work was designed to better quantify cost-benefit tradeoffs and risk reductions when layering different security technologies on wind energy industrial control system, operational technology networks. Standardized step-by-step attack scenarios were drafted for adversaries with remote and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Securing renewable energy facilities such as solar farms and wind turbines is essential to preventing disruptions in clean energy generation [151]. Empirical evidence from a study on a cyber-physical wind energy site demonstrated the effectiveness of cybersecurity technologies in preventing physical impacts and disruptions to the power system [152]…”
Section: Renewable Energy Facility Securitymentioning
confidence: 99%
“…Securing renewable energy facilities such as solar farms and wind turbines is essential to preventing disruptions in clean energy generation [151]. Empirical evidence from a study on a cyber-physical wind energy site demonstrated the effectiveness of cybersecurity technologies in preventing physical impacts and disruptions to the power system [152]…”
Section: Renewable Energy Facility Securitymentioning
confidence: 99%
“…In addition, along with other physical devices, batteries are used to stock the excess energy in the simulated model. On the operational technology network for wind energy, Sandia National Laboratories and Idaho National Laboratory deployed cutting-edge cybersecurity tools, such as security, orchestration, automation, and response (SOAR) tools that have an impact on the physical grid system components and stop the adversary kill chain [159].…”
Section: Sg Simulation For Renewable Energy Sourcesmentioning
confidence: 99%
“…In addition, along with other physical devices, batteries are used to stock the excess energy in the simulated model. On the operational technology network for wind energy, Sandia National Laboratories and Idaho National Laboratory deployed cutting-edge cybersecurity tools, such as security, orchestration, automation, and response (SOAR) tools that have an impact on the physical grid system components and stop the adversary kill chain [154].…”
Section: Sg Simulation For Renewablementioning
confidence: 99%